Digital Vote: Assessing Constitutional Compliance of Electoral Technology Laws and Verifiability of votes in Kenya - Charles Ochieng' Oguk,; Jane Juma, (IJRDO - Journal of Social Science and Humanities Research, 2025)
The integrity of the electoral process is the bedrock of any thriving democracy, a principle deeply enshrined in the Constitution of Kenya-2010, particularly under Articles 10, 81, and 86(a), which mandate free, fair, transparent, verifiable, and accountable elections. Despite this robust constitutional mandate, the current electoral system, governed by the Elections Act of 2011 and its subsidiary regulations, faces critical challenges. A fundamental issue lies in the abstract nature of a vote once cast, rendering its traceability and contribution to the final tally a "matter of faith," thereby making practical verification impossible. This research aims to critically analyze the effectiveness of the Elections Act, 2011, and the Elections (Technology) Regulations in ensuring compliance with these constitutional principles. Through an examination of recurring presidential election disputes in Kenya (2013, 2017, 2022) and the inherent limitations of the current legal framework, especially concerning the undefined "digital vote" and the contentious Section (83) of the Elections Act, 2011, this paper argues that the existing system fundamentally undermines electoral integrity and the core tenets of the Social Contract Theory. It highlights the significant gap between constitutional ideals and practical reality, leading to eroded public trust, political instability, and challenges to arbitrary vote attribution. The paper concludes with a call for comprehensive reform to align Kenya's electoral laws with its constitutional imperatives for a truly transparent, accountable, and verifiable democratic process.